PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL COOPERATIVE LEARNING DI KELAS XII SMKN 2 PEKANBARU - KAMAL MAJDI (JURNAL ILMIAH MAKSITEK, 2022)
The problem in this study is that learning is still dominantly centered on the teacher. This is because generally lessons on software application and building interior design are presented conventionally with very minimal student involvement, less attractive to students and boring. This study aims to describe the increase in student learning outcomes in class XII using the cooperative learning model at SMKN 2 Pekanbaru. This type of research is classroom action research. This research was conducted at SMKN 2 Pekanbaru. The research was conducted in two cycles with 4 (four) stages, namely planning, implementing, observing, and reflecting. The subjects in this study were 35 class XII students at SMKN 2 Pekanbaru. Data collection techniques through class observation and documentation. The data analysis technique that guides data processing uses the percentage (%) technique. The results of this study indicate that learning using the cooperative learning model can improve student learning outcomes which can be seen in the average learning outcomes of cycle II which is more increased than cycle I, where in cycle I the average obtained is 75. While cycle II the average obtained is 84.